Meningkatkan Penguasaan Kosakata Menggunakan Flashcard pada Siswa Kelas VII SMPN 2 Kisaran - Rambe, Yuni Annisa Hafni; Rahma Yunita Ansi; Endang Dorisday Sitorus (ELP (Journal of English Language Pedagogy), 2025)
This study investigated the effectiveness of using flashcards to improve vocabulary mastery among seventh-grade students at SMP Negeri 2 Kisaran, who have demonstrated limited vocabulary knowledge due to difficulties in memorizing new words. The objective was to enhance students’ vocabulary through the implementation of flashcards as a learning tool. The study employed classroom action research based on the Kemmis and McTaggart model, conducted in two cycles comprising the stages of planning, action, observation, and reflection. A total of 30 students from class VII–7 participated in the study. Data were collected through observations and vocabulary tests. The results revealed a significant improvement in students’ vocabulary mastery, with the average test score increasing from 67.8 (33.3%) in Cycle 1 (categorized as low) to 82.8 (73.3%) in Cycle 2 (categorized as high). These findings indicate that the use of flashcards is an effective strategy for enhancing vocabulary acquisition among junior high school students.